Analisis Perubahan Ekonomi Masyarakat Sesudah Dan Sebelum Adanya Obyek Wisata Kebun Teh Bah Butong, Sidamanik, Kabupaten Simalungun, Sumatera Utara - Nedra Aulia (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
The purpose of this study was to analyze changes in the community's economy after and before the opening of the Bah Butong Tea Garden tourism object to the public. The descriptive quantitative data analysis method includes descriptive variable tests and paired sample t-tests. The results of this study indicate that the paired t-test difference test on household expenditure variables type of work means there are significant differences after and before the opening of the Bah Butong Tea Garden tourism object to the public. Against residents who are tea farmers, traders, photographers, parking attendants, section heads, and public toilet guards at the Bah Butong Tea Garden tourism object after its opening to the public. There are economic changes that have a positive impact, namely increasing revenue from the tourism sector, increasing income from business activities carried out by the community at the Bah Butong Tea Garden tourism object, the production of food, beverages, parking tickets, entrance tickets, people already have permanent jobs and can increase their income. the standard of living of the people in the Bah Butong Tea Garden tourism object.